Granulosis rubra nasi - a case report. A literature review - Brzezinski Piotr; Poklękowska Katarzyna (Our Dermatology Online, 2011)
Granulosis Rubra Nasi (GRN), a rare childhood dermatitis that was also defined as "Acne papulo-rosacea of the nose". Is an inflammatory dermatosis which consists on erythema, papules and itch. The hyperhidrosis the most conspicuous features of the disease and small beads of sweat and erythema on the tip of the nose may often occur. Sometimes small red papules and comedo-like lesions may be present. Etiology is unknown. lt's uncommon, chronic process and benign course. Usually subsides spontaneously at adolescence. The treatment is symptomatic and cosmetic. An 14-year-old boy presented with erythematous lesions over the nose of childhood duration without sensitivity to sunlight. Physical examination showed also excessive sweating of the nose, and erythema of the nose covered by small pustules, papules ang macules. The patient responded well to low doses of oral Isotretinoine. Should remember GRN could be a complication of hyperhidrosis.